MENSTRUAL EDUCATION TO ENHANCE KNOWLEDGE IN FEMALE ADOLESCENTS AGED 8–14 YEARS - Maulina, Rufidah; Kusumawardhani, Evina; Lestari, Efrila Antika Puji; Putri, Eka Yunanda Permata; Puteri, Elshinta Damayanti Antoro; Puspitasari, Evvy Anjar; Nabila, Fanny Fatatin; Ratri, Fressyana Kusuma; Jamiilah, Jihan Abdillah Nur; Mujahida, Karisma Sakina; Meinawati, Khairunnisa; Mazaya, Laily (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Vulnerable groups include several groups of individuals who experience obstacles or restrictions in achieving a decent standard of living. One of the groups included in the vulnerable group is girls living in orphanages. They have reproductive rights that must be fulfilled, for example getting education and information related to reproductive health. One of them is related to menstrual education. This activity was carried out at the LKSAM Bina Umat Orphanage on May 19, 2024.The purpose of this community service is to increase the knowledge of adolescent children in preparing for menstruation. The method of implementing community service is carried out by brainstorming which contains counseling on menarche, menstruation, dysmenorrhea and personal hygiene using educational media flipcharts and posters, as well as pre-test and post-test to evaluate the level of understanding of the material. The research method used was total sampling technique. This activity involved the sample students used, namely 15 children from the LKSAM Bina Umat orphanage with an age range of 8-14 years.  The results of the activity are: of the 16 targeted participants, 15 participants or 93.75% attended the counseling activities; the average pre-test score was 81.25% and the post-test was 92.5%, it can be seen that there was an average increase of 11.25%. From this activity, it can be obtained that there has been an increase in understanding of menstrual readiness in children aged 8-14 years at Panti